Dental Treatment and Quality of Life in Rare Syndromes - Mehmood Ahmad Rana, Anam Akram, Danial Husain, Humara Iqbal, Waheed Said, Saqib Mahmood Khan, (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Rare syndromes encompass a diverse group of genetically inherited disorders, each characterized by a unique combination of clinical features and underlying genetic anomalies Objectives: The main objective of the study is to find the dental treatment and quality of life in rare syndromes Material and methods: This prospective cohort study was conducted from January 2022 to January 2023 atBakhtawar Amin Medical and Dental college Multan, involving a total of 120 participants diagnosed with various rare syndromes.A purposive sampling method was employed to recruit participants, where individuals with rare syndromes receive specialized care. Inclusion criteria consisted of individuals aged 6 to 40 years with a confirmed diagnosis of a rare syndrome. Exclusion criteria encompassed individuals with cognitive impairments that hindered self-reporting, those with severe medical conditions precluding dental treatment, and participants who did not provide informed consent Results: A total of 120 participants diagnosed with rare syndromes were included in the study. The age distribution ranged from 6 to 40 years, with a mean age of 22.8 ± 8.6 years. The gender distribution included 62 males (51.7%) and 58 females (48.3%) Conclusion: It is concluded that this study highlights the transformative impact of tailored dental treatment interventions on the quality of life of individuals with rare syndromes. Addressing dental anomalies through multidisciplinary collaboration can alleviate functional limitations, pain, and psychosocial challenges, ultimately enhancing overall well-being. Keywords: Dental treatment, Quality , Life, Rare Syndrome, Diagnosis